2004
DOI: 10.1007/s00198-004-1743-x
|View full text |Cite
|
Sign up to set email alerts
|

A model of osteoporosis impact in Switzerland 2000–2020

Abstract: The aim of our study was to develop a modeling framework suitable to quantify the incidence, absolute number and economic impact of osteoporosis-attributable hip, vertebral and distal forearm fractures, with a particular focus on change over time, and with application to the situation in Switzerland from 2000 to 2020. A Markov process model was developed and analyzed by Monte Carlo simulation. A demographic scenario provided by the Swiss Federal Statistical Office and various Swiss and international data sourc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
1
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 42 publications
1
30
1
2
Order By: Relevance
“…Whilst the values of Burge et al [29], Schwenkglenks et al [31] and Sanders et al [4] came relatively close to the values we determined, the results of Borgström et al [30] were considerably below the cost increase we determined up to 2050. But these comparisons must be handled with care, since differing population mixtures and differing demographic prognoses limit international comparability.…”
Section: Discussioncontrasting
confidence: 40%
“…Whilst the values of Burge et al [29], Schwenkglenks et al [31] and Sanders et al [4] came relatively close to the values we determined, the results of Borgström et al [30] were considerably below the cost increase we determined up to 2050. But these comparisons must be handled with care, since differing population mixtures and differing demographic prognoses limit international comparability.…”
Section: Discussioncontrasting
confidence: 40%
“…Recent investigation has revealed that bone and fall-related risk factors might be of greater importance in the etiology of fractures than was assumed previously [3]. Because of the growing proportion of elderly people in Western societies, the number of these fractures can be expected to increase further in the coming years [4][5][6][7]. Adults who suffer fractures of the distal radius are at increased risk of further osteoporosis-related fractures and represent a high-risk group in whom therapy is needed to reduce the risk [7].…”
Section: Introductionmentioning
confidence: 99%
“…The total direct medical cost of all hospitalized osteoporotic fractures can be extrapolated to CHF 524 mio, to which the inpatient rehabilitation and nursing home costs should be added. These represent approximately 50% of the total cost of the inpatient management of osteoporotic fractures, as already published earlier by our group [38], so that the total cost of treating hospitalized osteoporotic fractures in Switzerland exceeded CHF 1 billion in 2008. Cost estimates calculated in the present analysis are based on the nationwide average real cost per day of hospitalization and not on discipline-specific costs or Diagnosis Related Groups (DRGs).…”
Section: Cost Of Hospitalizationsmentioning
confidence: 57%